The content of the organization of correctional and pedagogical assistance in Uzbekistan - Raximova Muniraxon Ilhomovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
early identification of Disabled People, their involvement in special education, - comprehensive development. in the spirit of humanism, self-sacrifice, information is given about upbringing, training, vocational guidance, prevention and recovery of disability, preparation for life and adaptation to the Society of normally developed people.